KONDISI FISIK OLAHRAGA BULUTANGKIS - Nimrot Manalu; Zen Padli; Rizky salomo sitorus; Wira Hadi Arie; Muhammad Rifki Purba; M. Aidil Bimantara Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
If the athlete wants to have a good physical condition, then the player or athlete must improve their physical condition so that an athlete is able and easy to perform a technique correctly and well, and not easily exhausted when participating in training or competitions, training can be passed appropriately, and something that is not wanted or obstacles, can be solved by the desire to learn athletes , and follow the exercises appropriately and correctly.This research method is conducted by studying literacy or literature riview by looking for the source of research results from books and research articles on the physical condition of badminton.Physical condition status for a badminton or badminton player will be able to provide a point or value for the achievement of targets or targets in order to enter the national court in accordance with the criteria determined by the national court.Good athletes must master the various supporting components of achievement. To know the extent of an athlete's physical condition, one of them is affected by the right recovery pattern.Not only that, the coach is also a support that is needed by an athlete to improve the performance of an athlete.A professional trainer has competence in his field of expertise.